Functional Requirement Design for Optimizing Tourism Promotion of DKI Jakarta based on Descriptive Research Method - Wastam, Jumail; Prasetya, Eka Budhy; Latifah, Retnani (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
This study presents data collected as sample from two places of tourism spots, TMII and MONAS. Furthermore, additional data has also been collected from public places such as campuses to support current data collection. The data is collected in order to recognize the visitorsâ responses according to their tourism information needs in preparing their traveling activities. Descriptive research method adopted using self-designed questionnaires focusing on âwhatâ is applied to investigate the questions which are related with the topic of the study. The results of data analysis would be referred as foundation in designing the system functionalities required to develop an application for the future development. Furthermore, more data is observed from some data resources such as Central Bureau of Statistics (BPS) of DKI Province and Global Destination Cities Index to recognize the performance of DKI Jakarta in receiving visitors within the last three years compared to other cities in some neighboring countries such as Bangkok, Kuala Lumpur and Singapore. Thirty respondents are involved in the study to identify what potential information which can be explored. The information which is related to visitorsâ travel preparation becomes imperative to be analyzed to optimize the tourism promotion. Descriptive research method helps researchers in obtaining data on functional needs according to the current state of society, in the scope of travel activities and preparations. The system design viewed from the functional needs shows what people can do based on the results of the analysis.